Analysis of Product Quality and Customer Satisfaction: A Case Study of the Automotive Parts Industry - Hsu, Chu-chuan; Chen, Shun-Hsing; Feng, Xiu-chun (International Journal of Financial, Accounting, and Management, 2024)
Purpose: The automobile parts industry is a technologically and capital-intensive industry with a vast supply chain that influences various related industries. Many Taiwanese automobile parts manufacturers are small to medium-sized enterprises, with a complete industry supply chain. They possess the advantages of small-scale, diversified, and flexible manufacturing, enabling them to compete internationally and potentially enter the supply chains of international car manufacturers. Good product quality is favored by customers, and there is a correlation between product quality and customer satisfaction. The design of product attributes is primarily aimed at meeting customer needs. To outperform competitors, companies can establish additional value in their products to actively please customers and even enhance customer loyalty. This study investigates the differences in demographic variables on product quality and customer satisfaction and analyzes the degree of correlation between the two variables. Research Methodology: This study adopts a questionnaire survey method as the tool for data collection. The questionnaire is designed based on the research objectives, focusing on customer satisfaction, to explore the satisfaction levels of the case company's relevant dimensions among existing customers and compare them with customer expectations, providing recommendations accordingly. The subjects of this study are companies in the automotive parts industry with a capital of over ten million. The questionnaire was distributed from April to May 2022, with a total of 170 questionnaires distributed and 157 collected, resulting in a response rate of 92.35%. Results: The study results indicate significant differences in gender, marital age, education level, and seniority concerning product quality and customer satisfaction, but no significant differences were found in the organizational size of the company. Subsequent Pearson correlation analysis reveals a Pearson correlation coefficient of 0.85, indicating a high correlation between product quality and customer satisfaction. This suggests that excellent product quality influences customer satisfaction. Limitations: This study focused on the case of the automotive parts industry to explore the differential analysis of product quality and customer satisfaction. The research results are only applicable to the automotive parts industry. Contribution: The study found a positive correlation between product quality and customer satisfaction. Therefore, the capability to enhance product quality, making products attractive and creating differentiated brand value, is actively pursued by companies as a development goal. The results of this study are consistent with previous research findings. With more streamlined product quality and detailed production history information, consumers' willingness to purchase increases. As consumer purchasing intention rises, so does brand loyalty, leading to increased profitability and surpassing competitors.